2005
DOI: 10.5194/angeo-23-499-2005
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Alfvén waves in the night-side ionospheric Alfvén resonator at mid-latitudes

Abstract: Abstract.A numerical solution of the problem on dynamics of shear-mode Alfvén waves in the ionospheric Alfvén resonator (IAR) region at middle latitudes at nighttime is presented for a case when a source emits a single pulse of duration τ into the resonator region. It is obtained that a part of the pulse energy is trapped by the IAR. As a result, there occur Alfvén waves trapped by the resonator which are being damped. It is established that the amplitude of the trapped waves depends essentially on the emitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…According to these calculations, dependence of resonant frequencies on harmonic number n was approximated as x n =X A ' ð2n þ 1Þ=3, whereas the interval between eigenfrequencies was Dx=X A ' 2=3, where X A is the resonator fundamental frequency. In our model the ratio Dx=X A ¼ 1:18 for UT = 4, and 0.86 for UT = 16, which is different from 0.66 in (Alpatov et al 2005).…”
Section: Diagnostics Of the Upper Ionosphere With The Use Of Iar Specmentioning
confidence: 58%
See 1 more Smart Citation
“…According to these calculations, dependence of resonant frequencies on harmonic number n was approximated as x n =X A ' ð2n þ 1Þ=3, whereas the interval between eigenfrequencies was Dx=X A ' 2=3, where X A is the resonator fundamental frequency. In our model the ratio Dx=X A ¼ 1:18 for UT = 4, and 0.86 for UT = 16, which is different from 0.66 in (Alpatov et al 2005).…”
Section: Diagnostics Of the Upper Ionosphere With The Use Of Iar Specmentioning
confidence: 58%
“…The factor in the linear regression a ¼ À0:95 is also very close to 1. Therefore, the dependence of TEC (measured in TECU = 10 16 m À2 ) on Df is well approximated by formula We compare our modeling results with the spectral relationships from Alpatov et al (2005) numerical model based on approximation of n A ðzÞ and a perfectly reflecting E-layer. According to these calculations, dependence of resonant frequencies on harmonic number n was approximated as x n =X A ' ð2n þ 1Þ=3, whereas the interval between eigenfrequencies was Dx=X A ' 2=3, where X A is the resonator fundamental frequency.…”
Section: Diagnostics Of the Upper Ionosphere With The Use Of Iar Specmentioning
confidence: 97%
“…here T 0 is the Alfvén travel time between the resonator walls, or the bounce period in terms of Alpatov et al (2005); l bottom and l top are the positions of the resonator lower and upper walls, respectively; A(l) is the Alfvén speed…”
Section: Calculations Based On the Standard Iri-2012 Modelmentioning
confidence: 99%
“…Pokhotelov et al (2000) found frequency dispersion of the IAR eigenmode due to the Hall conductivity. Alpatov et al (2005) calculated the characteristics of the Alfvén waves propagating between the Earth's surface and the upper ionosphere using a numerical model. They analyzed two types of external wave sources: pulse and monochromatic oscillations.…”
Section: Introductionmentioning
confidence: 99%